Treatment funding source and educational level are important prognostic factors for patients with diffuse large B-cell lymphoma in the state of São paulo, Brazil: Analysis of a large real-world data. - Cle, Diego; Gaiolla, Rafael [UNESP]; Correa-Netto, Nelson; Ziegelmann, Patricia; Castro, Douglas; La Scala, Cintia; Silveira, Iago; Duffles, Guilherme (American Society of Hematology, 2025)
Abstract Introduction: Diffuse large B-cell lymphoma (DLBCL) is among the ten most prevalent cancers in Brazil. Although the country has numerous specialized oncology centers, comprehensive population-level data on DLBCL outcomes are limited. International studies report a 5-year overall survival (5y OS) rate of 60–70%, but these estimates may not accurately reflect the Brazilian reality, where access to diagnosis and treatment varies substantially. Since 2014, the incorporation of rituximab in the CHOP regimen has enabled outcome comparisons across healthcare systems. However, Brazil's dual public-private healthcare structure introduces significant socioeconomic disparities that may influence survival. This study aimed to assess 5y OS in DLBCL patients treated in Brazil and to explore how sociodemographic factors, particularly treatment funding source and education level, impact survival in a real-world setting. Methods: This retrospective cohort study is based on real-world data extracted from the Hospital Cancer Registry of the State of São Paulo (RHC-SP). RHC-SP is an anonymized clinical registry of care for previously untreated patients and includes all public or private hospitals accredited by the Brazilian Ministry of Health for high-complexity oncology care, and private volunteer hospitals, totaling 86 hospitals in the state. The collected data included sociodemographic characteristics, clinical features, and treatment details. The primary endpoint was 5y OS. Multivariable Cox proportional hazards models were used to assess the association between OS and covariates, including treatment funding (public vs. private), sex, age group (18-64 vs. 65-99 years), educational level (≤8 vs. >8 years of education), and time to treatment initiation (TTI) after diagnosis (≤60 vs. >60 days). Interaction terms between treatment funding source, sex, and age group were also included. Results: A total of 1,962 patients were included, with 1,681 (85.7%) treated in the public healthcare system. The median age at diagnosis was 59 years (range, 18-96 years), and 52.5% were male. Patients aged 18–64 comprised 62.7% of the cohort, and only 32.9% had more than 8 years of education, with a significant disparity between private (55.2%) and public (29.1%) settings. The median time from diagnosis to treatment was 43 days. After a median follow-up of 5.3 years (95% CI, 5.2 - 5.6), the estimated 5y OS for the entire cohort was 52.7% (95% CI, 50.4% - 55.1%). The 5y OS for patients treated at a private center was 54.9% (95% CI, 47% - 64%) and 51.6% (95% CI, 49.1% - 54.2%) for patients of the public system. Multivariable analysis revealed disparities in 5y OS between treatment funding sources, with poorer outcomes observed in the public health system. This disparity was more pronounced in women (HR = 3.06; 95% CI, 1.88 - 4.98; p < 0.001) than in men (HR = 1.74; 95% CI, 1.14 - 2.64; p < 0.05). In the private healthcare system, women exhibited a significantly better 5y OS compared to men (HR = 0.51, IC = 0.33 - 0.78, p < 0.01). However, this difference was not observed in the public healthcare system (HR = 0.90, IC = 0.78 - 1.04, p = 0.142). Advanced age was associated with worse 5y OS, with a greater increase in hazard in the private system (HR = 3.05; 95% CI, 1.95 - 4.78) than in the public system (HR = 1.60; 95% CI, 1.38 - 1.85; p < 0.001). A higher educational level (HR = 0.68; 95% CI, 0.57 - 0.81; p < 0.001) and higher TTI (>60 days) (HR = 0.62; 95% CI, 0.53 - 0.72; p < 0.001) were independently associated with improved 5y OS, regardless of the treatment funding. Conclusions: This large, real-world analysis reveals significant socioeconomic disparities in outcomes for DLBCL in São Paulo state, Brazil, the most economically developed state in the country. Treatment within the public healthcare system and lower educational attainment were associated with lower 5y OS. The survival gap between public and private systems was most pronounced among women. A longer time to treatment initiation was related to better survival, which could be explained by a less aggressive disease presentation. Our findings emphasize that, beyond tumor biology, socioeconomic factors are critical determinants of prognosis in DLBCL. Given that the majority of the state's population relies on publicly funded healthcare, urgent health policies are needed to address these inequities and improve patients' survival.